Réponses

2014-02-12T17:06:24+01:00
Je peux t'aider que jusqu'a la b. Arés je ne sais pas

a: 4(5x-2)=7-(4-3x)
20x-8=7-4+3x
20x-8-3x=3+3x-3x
17x-8=3
17x-8+8=3+8
17x=11
x=17/11
x= environ 1,5

b. x-7(3x-5)=2x-5(2-3x)
x-21x+35=2x-10+15x
20x+35=-10+17x
20x+35-17x=10+17x-17x
3x+35=10
3x+35-35=10-35
3x=-25
x=3/-25
x=-0,12


b x-7(3x-5) = 2x-5(2-3x)
x-21x+35 = 2x-10+15x
x-21x-2x-15x = -10-35
-37x = -45
37x = 45
x= 45/37
a 4(5x-2) = 7-(4-3x)
20x-8 = 7-4+3x
20x-3x = 7-4+8
17x = 11
x = 11/17
c (x+7)(2x-3) = (2x-1)(x+4)
2x2 + 14x - 3x -21 = 2x2 - x + 8x -4
2x2-2x2+14x-3x+x-8x = 21 -4
4x = 17
x=17/4
d (5x-8)/6 = (3x+7)/2
(5x-8)*2 = (3x+7)*6
10x -16 = 18x + 42
-58 = 8x
x = -58/8
x = -29/4
e (2x+1)/4 - (5x-3)/12 = (x+7)/3
(2x+1)*3/12 - (5x-3)/12 = (x+7)/3
(2x+1)*3/12 - (5x-3)/12 = (x+7)*4/12
(6x+3)/12 - (5x-3)/12 = (4x+28)/12
(6x - 5x + 3 + 3) / 12 = (4x+28)/12
x = 4x+28-6
x - 4x = 22
-3x = 22
x = -22/3